[Afisz. Incipit] Regulamin pracy. (Gdańsk : [wydawca nieznany], 1949)
Afisz z treścią regulaminu.
Keywords: Regulamin wewnętrzny -- Polska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (woj. pomorskie); Druki ulotne -- 1945-1970.; Druki ulotne